Supply chain management in advance tech energy edibles india. - KRISHNAMOORTHY, MR. D.; KORAH, MISS JAYSHREE (The journal of contemporary issues in business and government, 2020)
This article is all about Supply Chain Management in “Advance Tech Energy Edibles India Ltd.” is the research work that deals with different processes and techniques adopted by various FMCG retail Organizations, specifically and to find gaps that needed to be filled for improvement in FMCG retail. Supply chain management for retail companies strives to control product quality, inventory levels, timing and expenses. A clear supply chain strategy with differentiated service offerings and delivery terms is essential to optimizing the balance of cost and required customer service. An integrated approach considering supply, production, transportation, operations and service is crucial to design the most competitive retail logistics concept for the company. We collected primary data and secondary data about oil manufacturing and how they make logistics on it. To study the influence of demographic variables on customer perspective. To know the relationship between profession and delivery. The article was basically based on the customer's view on the logistics system in the edible oil industry but it consisted of so many things which I learnt, like how to manage people, how to get maximum output from the people and how to make a balance in sales. If a company’s product is good then it does not have to worry about things and competitors.